Taking Vulnerability into Account for the Reallocation of SDRs? - Alban Cornier; Laurent Wagner (Fondation pour les études et recherches sur le développement international (FERDI), 2022)
The voluntary reallocation of a portion of Special Drawing Rights (SDRs) from advanced countries to developing countries is potentially an important transformation in the international monetary system. Attention has so far been focused on the channels of this reallocation, because of the need to preserve the reserve asset nature of SDRs. The IMF is considering three options (Pazarbasioglu and Ramakrishnan, 2021). First, it is proposed to increase the size of the Poverty Reduction and Growth Trust (PRGT). Second, the IMF could create a new IMF-administered Resilience and Sustainability Trust, or RST: The proposed RST would support policy reforms to help build economic resilience and sustainability in low-income countries and small states, as well as vulnerable middle-income countries. Third, the IMF could channel SDRs to other prescribed SDR holders, comprising 15 organizations including the World Bank, some regional central banks, and multilateral development banks. The three options are non-mutually exclusive.
Keywords: 330